When the market drives you crazy: Stock market returns and fatal car accidents - Corrado Giulietti; Mirco Tonin; Michael Vlassopoulos (Global Labor Organization (GLO), 2018)
The stock market influences some of the most fundamental economic decisions of investors, such as consumption, saving, and labor supply, through the financial wealth channel. This paper provides evidence that daily fluctuations in the stock market have important -and hitherto neglected- spillover effects in another, unrelated domain, namely driving. Using the universe of fatal road car accidents in the United States from 1990 to 2015, we find that a one standard deviation reduction in daily stock market returns is associated with a 0.5% increase in the number of fatal accidents. A battery of falsification tests support a causal interpretation of this finding. Our results are consistent with immediate emotions stirred by a negative stock market performance influencing the number of fatal accidents, in particular among inexperienced investors, thus highlighting the broader economic and social consequences of stock market fluctuations.
Keywords: D91; R41; G41; 330; stock market; car accidents; emotions